Associação entre marcadores da resposta inflamatória e a imunopatogênese de agentes infecciosos de natureza viral (Vírus da dengue, HTLV-1 e HTLV-2) e bacteriana (Chlamydia trachomatis e Chlamydia pneumoniae) - FEITOSA, Rosimar Neris Martins (Universidade Federal do Pará, 2014)
The genetic basis of diseases is frequently studied aiming the polymorphisms of cytocine genes. The present study investigated markers of the inflammatory response associated to the course of infection and disease caused by viruses and bacteria. Serum levels (measured by an ELISA assay) and the polymorphisms (using PCR, RFLP and allele specific PCR) of TNF-α (-308), TNF-β (+252), IFN-γ (+874) and C reactive protein were measured among persons with febrile disease, infected by dengue virus (n=80), not infected by DV (100), a group of HTLV infected (30 symptomatic and 47 asymptomatic), a group with coronary disease (58 seroreactive to Chlamydia and 31 with negative serology) and a control group (99 persons with no reaction to DV, HTLV and Chlamydia). No group showed association with demographic informations. Dengue virus 3 (66.2%) and HTLV-1 (90% symptomatic and 76.6% asymptomatic persons) were the most frequent agents found among their groups. The majority of those with coronary disease (65.1%) presented antibodies to Chlamydia (39.6% to C. trachomatis and C. pneumoniae, 58.6% solely to C. trachomatis and 1.7% to C. pneumoniae). Statistically significant levels of differences were found among: (i) serum levels of TNF-β, IFN-γ and PrtCR of positive and negative dengue and control groups (p< 0,01); (ii) serum levels of TNF-α, TNF-β and IFN-γ of HTLV (including its types) and control groups; (iii) serum levels of TNF-α, TNF-β, IFN-γ and PrtCR among patients with coronary disease, serum reactive to Chlamydia, and the control group; (iv) the presence of antibodies to C. trachomatis and C. pneumoniae and the control group comparing TNF-β, IFN-γ and PrtCR. Genotypic frequency distributions were statistically significant for the polymorphisms: (i) of TNF-α (p=0,0494) and IFN-γ (p= 0,0008) genes among positive, negative and control dengue groups and to IFN-γ (p= 0,0007) among groups DEN 1, DEN 2, DEN 3 and controls; (ii) of IFN-γ gene (p= 0,0023) among the group of patients with coronary disease and sero reactivity to C. trachomatis e C. pneumoniae, as well as to the mono reactants in the comparison between the positivity to C. trachomatis and the control group.